SOSIALISASI OPTIMASI PERAN BADAN USAHA DESA (BUMDES) DI DESA LIWULAGANG, KECAMATAN NAGAWUTUNG, KABUPATEN LEMBATA - Jelamu, Maria Gratia Wildiyani; Lamadoken, Desriana Meme Ema; H. Molan, Kristianus Simon; Kelen, Veronika B.; Lamawuran, Yosef Dionisius; Ethelbert, Yohanes Kornelius; Sius, Karolus Tatu (Jurnal Pengabdian Masyarakat Sabangka, 2025)
Village-Owned Enterprises (BUMDes) are village economic institutions that are formed based on the needs and potential of the village to increase community awareness and encourage independent local economic development. The presence of BUMDes is one of the important instruments in order to support participatory, sustainable, and local potential-based village development programs. This Community Service aims to examine in depth the role of BUMDes in village development and its contribution to improving community welfare. The community service is conducted with a descriptive qualitative approach through literature studies, documentation, and data collection from various relevant sources. The results of the study show that BUMDes play a strategic role in village economic development through opening employment opportunities, increasing community income, productive management of natural resources, and creating new businesses that are in accordance with local characteristics. BUMDes also strengthens the village's institutional capacity through strengthening organizational structure, business planning, and transparent and accountable financial governance. Furthermore, BUMDes serves as a bridge between the village government and the community in the development process,